Pulmonary artery sling anomaly presenting with unilateral lung hyperinflation: A case report - Şahin, Hilal; Pekçevik, Yeliz (The Turkish Journal of Pediatrics, 2018)
Left pulmonary artery sling is a rare congenital pulmonary artery anomaly which presents with tracheal compression due to vascular ring formation. Rarely, patients may present with hyperinflation or collapse of a lung unilaterally.We present a one-month-old infant with dyspnea who had a hyperinflated left lung and collapsed right lung. Computed tomography (CT) angiography demonstrated pulmonary sling causing compression of proximal parts of right and left main bronchi. This case highlights the importance of three-dimensional CT angiography in evaluation of thoracic vascular anomalies associated with tracheobronchial pathologies.